2020
DOI: 10.1039/c9ra08673k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ethanol production from sugarcane molasses by industrially engineered Saccharomyces cerevisiae via replacement of the PHO4 gene

Abstract: Replacement of a novel candidate ethanol fermentation-associated regulatory gene, PHO4, from a fast-growing strain through a novel strategy (SHPERM-bCGHR), is hypothesised to shorten fermentation time and enhance ethanol yield from sugarcane molasses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Sugarcane molasses (SCM) is the most traditional feedstock for ethanol production in Brazil and India, which is a dark brown liquid obtained as a by-product during sugarrefining process. A good amount of sugar (50-60%) remains in SCM affecting the revenue of the process adversely, which necessitates its sugar content to be converted into ethanol to take full advantage of sugarcane [53,54]. SCM is comprised of 80-85°brix, 44-60% total sugars, 31-34% sucrose, 16-17% reducing sugars, 12.69% ash (wet weight), amino acids, and minerals e.g., 300-12000 ppm potassium, 150-2000 ppm calcium, and 80-3900 ppm magnesium with pH of 5-5.8 [54].…”
Section: Sugary Feedstocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugarcane molasses (SCM) is the most traditional feedstock for ethanol production in Brazil and India, which is a dark brown liquid obtained as a by-product during sugarrefining process. A good amount of sugar (50-60%) remains in SCM affecting the revenue of the process adversely, which necessitates its sugar content to be converted into ethanol to take full advantage of sugarcane [53,54]. SCM is comprised of 80-85°brix, 44-60% total sugars, 31-34% sucrose, 16-17% reducing sugars, 12.69% ash (wet weight), amino acids, and minerals e.g., 300-12000 ppm potassium, 150-2000 ppm calcium, and 80-3900 ppm magnesium with pH of 5-5.8 [54].…”
Section: Sugary Feedstocksmentioning
confidence: 99%
“…A study was reported for fermentation of SCM containing 390 g/l total sugars with optimum urea (nitrogen source) and inoculum (S. cerevisiae) dosage at 4 and 0.5 g/l, respectively, at 35°C resulting into an ethanol concentration of 87 g/l with a fermentation efficiency of 85.12% [56]. Maiti, Rathore, Srivastava, Shekhawat, and Srivastava [57] investigated another study of fermentation of SCM containing initial total sugars of 216 g/l using 10% (v/v) inoculum size (Zymomonas mobilis 2427) at 31°C, and reported maximum ethanol yield of 59.59 g/l after 44 h. More recently, Wu, Chen, Cao, Lu, Huang, Lu, Chen, Chen, Guan, and Wei [53] studied the SCM fermentation with 70°C Brix value using industrially engineered strain S. cerevisiae MF01-PHO4 with 2 × 10 8 cells/ml, 0.2% (w/w) urea, and 0.02% (w/w) phosphoric acid at 30°C, and reported a maximum ethanol yield of 114.71 g/l after 24 h [53]. Another sugarrich feedstock which has been well studied for 1G ethanol production is sweet sorghum, which provides high ethanol yield per hectare (ha) of cultivation.…”
Section: Sugary Feedstocksmentioning
confidence: 99%
“…In a recent study, industrially engineered S. cerevisiae MF01-PHO4 was produced by protoplast formation and pho4 gene replacement, and the mutant strain was observed to be stable for up to 30 generations. An enhanced ethanol yield of 114.71 g/L was achieved with the genetically engineered strain, accounting for 5.30% increase in ethanol yield and 12.5% decrease in fermentation time (Wu et al, 2020). There is no clear evidence on side effects of genetically modified microorganisms on environment; thus, there is still a need to take preventive measures to ensure environmental safety.…”
Section: Strain Development For Improved Bioethanol Fermentationmentioning
confidence: 99%
“…Saccharomycetes is the biocatalyst of ethanol produced by sugarcane molasses. However, Yeast's optimum fermentative pH is 4.0-4.5 while sugarcane molasses are about 6.2 (Wu et al 2020). Therefore, a large amount of sulfuric acid should be added to reduce the acidity when diluting.…”
Section: Introductionmentioning
confidence: 99%